If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = -6x + 18 Reorder the terms: 10 + 2x = -6x + 18 Reorder the terms: 10 + 2x = 18 + -6x Solving 10 + 2x = 18 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 10 + 2x + 6x = 18 + -6x + 6x Combine like terms: 2x + 6x = 8x 10 + 8x = 18 + -6x + 6x Combine like terms: -6x + 6x = 0 10 + 8x = 18 + 0 10 + 8x = 18 Add '-10' to each side of the equation. 10 + -10 + 8x = 18 + -10 Combine like terms: 10 + -10 = 0 0 + 8x = 18 + -10 8x = 18 + -10 Combine like terms: 18 + -10 = 8 8x = 8 Divide each side by '8'. x = 1 Simplifying x = 1
| 2x^2(3x+1)=9 | | 7x-4+8=6x+8 | | y+(y+10)=24 | | -11+11x=21+9x | | 15=8x(x)-14x | | (3x+3)-(2+5)=9 | | 4(9x-4)+2(2x-7)-7x=3(3x-10)+5(x-22)-4 | | 9x-7=x^2 | | 6x-32=26+4x | | -7(m+2)=-14 | | f(x)=6x^4(1-x^2) | | 4u^2+14u+6=0 | | (2y^2)-9y+4=0 | | 2x+18=3x+6 | | 7c+4d=-21 | | 5b-9=11b+8 | | -91+3x=129-7x | | 2a-5a=4 | | -38-3x=-6x+40 | | 6a+9=2a+13 | | (7z+2)-(3z+5)=15 | | x+3.5=-4.02+2x | | 0.02=3*r^5-1 | | 3/4+3/5+7/10= | | 9x+2y-11=360 | | 9x+24=4x+164 | | 6x+14=-28 | | 2+5-3-x-3=x+3+x-4-2 | | (2*y+1)*5=35 | | 9x+2y=371 | | 10(x+4)=3(2x+5)+1 | | 24+1.2z=-2.4 |